Exercising A Case Study Research in Post-conflict Environment: Exploring the Struggle of the Coastal Farmer Union (PPLP) Opposing the Neoliberal Policy in the Kulon Progo Coastal Area, Indonesia (Open Society Conference, 2025)
Researching in a post-conflict context is challenging. Methodological issues such as research ethics and data-gathering approach are critical. The researcher must have appropriate measures to collect the data. My fieldwork, spanning five months, took place in six coastal villages in Kulon Progo, Special Region of Yogyakarta, Indonesia. This site is the home to the Coastal Farmer Union (the PPLP), which rejected the government's mining plan from 2006 on. Coastal dwellers are mostly farmers who cultivate the coastal land. To obtain the data I used a qualitative research method with a single case study approach. Many challenges hinder my fieldwork, such as being expelled from the PPLP meeting, being intimidated and stigmatized, and experiencing fears, trauma, and stress. Therefore, I exercise agile data-collection strategies, be more concerned with research ethics, and be self-motivated. I utilized participant observation, snowball sampling, in-depth interviews, and political action to gain information about the coastal farmer resistance. I employed participant observation, snowball sampling, open-ended interviews, and political action to gather information on the coastal farmer resistance. I exercised political action to engage with the informants through writing and publishing their struggles in a zine organized by activists who support their struggle. This creates trust in the informants. Using these strategies, I obtained the data, and I built social capital with my informants. This paper discusses my thesis’s methodological approach and how to conduct fieldwork in a post-conflict environment.